Bacterial Profile, Antibiotic Sensitivity and Resistance of Lower Respiratory Tract Infections in Upper Egypt - Gamal Agmy; Sherif Mohamed; Yaser Gad; Essam Farghaly; Hamdy Mohammadien; Hebba Rashed (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract BACKGROUND: Lower respiratory tract infections (LRTI) account for a considerable proportion of morbidity and antibiotic use. We aimed to identify the causative bacteria, antibiotic sensitivity and resistance of hospitalized adult patients due to LRTI in Upper Egypt. METHODS: A multicentre prospective study was performed at 3 University Hospitals for 3 years. Samples included sputum or bronchoalveolar lavage (BAL) for staining and culture, and serum for serology. Samples were cultured on 3 bacteriological media (Nutrient, Chocolate ,MacConkey's agars).Colonies were identified via MicroScan WalkAway-96. Pneumoslide IgM kit was used for detection of atypical pathogens via indirect immunofluorescent assay. RESULTS: The predominant isolates in 360 patients with CAP were S.pneumoniae (36%), C. pneumoniae (18%), and M. pneumoniae (12%). A higher sensitivity was recorded for moxifloxacin, levofloxacin, macrolides, and cefepime. A higher of resistance was recorded for doxycycline, cephalosporins, and ?-lactam-?-lactamase inhibitors. The predominant isolates in 318 patients with HAP were, methicillin-resistant Staphylococcus aureus; MRSA (23%), K. pneumoniae (14%), and polymicrobial in 12%. A higher sensitivity was recorded for vancomycin, ciprofloxacin, and moxifloxacin. Very high resistance was recorded for ?-lactam-?-lactamase inhibitors and cephalosporins. The predominant organisms in 376 patients with acute exacerbation of chronic obstructive pulmonary diseases (AECOPD) were H. influnzae (30%), S. pneumoniae (25%), and M. catarrhalis (18%). A higher sensitivity was recorded for moxifloxacin, macrolides and cefepime. A higher rate of resistance was recorded for aminoglycosides and cephalosporins CONCLUSIONS: The most predominant bacteria for CAP in Upper Egypt are S. pneumoniae and atypical organisms, while that for HAP are MRSA and Gram negative bacteria. For acute exacerbation of COPD, H.influnzae was the commonest organism. Respiratory quinolones, macrolides, and cefepime are the most efficient antibiotics in treatment of LRTI in our locality.